Unintended barriers: exploring first-generation and continuing-generation college students’ sense of belonging and their perceptions of instructors’ behaviors - Jones, Tucker Lamar (Kansas State University, 2021)
Prior research has shown that instructors often engage in behaviors that (for better or worse) substantially impact their students’ subjective experiences within the class. For example, recent research has shown that instructors’ subjective experiences during class are likely to “trickle down” and influence the subjective experiences of their students which, in turn, can impact students’ engagement and performance on assessments (Saucier et al., in press). Given the ease at which certain students (e.g., first-generation college students, students who feel like they do not belong in higher education) may be likely to misinterpret and react negatively toward common and unintentional instructor behaviors (e.g., low energy level, use of highly technical language), more research that explores the extent to which students’ generational status (i.e., being a first-generation vs. a continuing-generation college student) and/or overall sense of belonging in higher education is related to their perceptions of and anticipated responses to various instructor behaviors is needed. As such, two studies were designed to systematically examine the extent to which students’ generational status and/or the extent to which they feel like they do (or do not) belong in higher education is related to their perceptions of and anticipated responses toward various instructor behaviors. Study 1 examined the differences between first-generation and continuing-generation college students in their perceptions of and anticipated responses to instructor behaviors that are positive, neutral, or negative. Although there were no differences between these students in their perceptions of and anticipated responses toward the different instructor behaviors, the results from Study 1 clearly show the substantial impact that instructors’ behaviors can have on their students’ subjective experiences. Students in Study 1 tended to agree more strongly that they had especially favorable perceptions of and anticipated responses toward positive instructor behaviors than neutral or negative instructor behaviors. Study 2 examined the extent to which first-generation and continuing-generation college students’ overall sense of belonging is related to their perceptions of the same instructor behaviors that were used in Study 1. The results from Study 2 generally replicated those from Study 1, but also showed that sense of belonging is significantly related to first-generation and continuing-generation college students’ perceptions of and anticipated responses toward various instructor behaviors. More specifically, continuing-generation college students with a lower overall sense of belonging tended to rate positive instructor behaviors more negatively, whereas first-generation college students with a higher overall sense of belonging tended to rate negative instructor behaviors more favorably. Overall, the results from these studies contribute to the extant literatures on instructor behaviors, first-generation and continuing-generation college students, and students’ sense of belonging within higher education. Further, by identifying the instructor behaviors that (for better or worse) impact students’ subjective experiences during class, the results from the current investigation have the potential to inform professional development programs that will attempt to maximize positive instructor behaviors, minimize negative instructor behaviors, and, in doing so, enhance the subjective experiences for both students and instructors.
Keywords: First-generation college students; Sense of belonging; Instructor behaviors; Person perception